Knowledge management and its impact on Islamic Da’wah: a historical perspective - Abdul Ghafar Haji Don; Jaffary Awang (2009)
Knowledge culture” is part of Islam. Since the life of the Prophet Muhammad (pbuh), this culture has been given a priority through the implementation of the “concept of iqra’. Correct understanding of this concept in the Muslim community has contributed to the formation of the “Islamic Civilization”. The emergence of this civilization is partly due to the management of knowledge itself. An analysis of the history of Islamic knowledge has shown that the Muslim community gave priority to knowledge management. The development of institutions of higher learning, known as madrasah, such as ‘Madrasah Nizamiah’, the building of complete educational infrastructure, the translation works, the publication of many outstanding books such as ‘Ihya’ Ulumuddin’ by Imam Al-Ghazali, the commitment of the government to develop a system of learning and at the same time the active participation of government leaders and the Muslim intellectuals in academic discourses are some indicators of knowledge management. In line with that statement, this paper attempts to explore the issue of knowledge management from an Islamic perspective and its relationship with da’wah. The focuses of this article are the significance of knowledge, the historical background of knowledge management in Islam and finally some suggestions for the development of Islamic knowledge in the Muslim community.